Recent advances biodegradation and biosorption of organic compounds from wastewater: Microalgae-bacteria consortium - A review - Chan, Sook Sin; Khoo, Kuan Shiong; Chew, Kit Wayne; Ling, Tau Chuan; Show, Pau Loke (Bioresource technology, 2022)
[Display omitted] •Persistent organic pollutants beget adverse effects on environment and ecosystem.•Conventional organic wastewater treatment is highly complex and expensive.•Microalgae-bacteria synergy shows several advantages to the economy and environment.•Microalgae-bacteria consortia is a latent wastewater treatment to remove POPs.•Mechanisms involved mainly via biosorption, bioaccumulation and biodegradation. The litter of persistent organic pollutants (POPs) into the water streams and soil bodies via industrial effluents led to several adverse effects on the environment, health, and ecosystem. For the past decades, scientists have been paying efforts in the innovation and development of POPs removal from wastewater treatment. However, the conventional methods used for the removal of POPs from wastewater are costly and could lead to secondary pollution including soil and water bodies pollution. In recent, the utilization of green mechanisms such as biosorption, bioaccumulation and biodegradation has drawn attention and prelude the potential of green technology globally. Microalgae-bacteria consortia have emerged to be one of the latent wastewater treatment systems. The synergistic interactions between microalgae and bacteria could proficiently enhance the existing biological wastewater treatment system. This paper will critically review the comparison of conventional and recent advanced wastewater treatment systems and the mechanisms of the microalgae-bacteria symbiosis system.